KAIDAH PEMBENTUKAN KATA ASAL BAHASA WARIA - Linarti Linarti (EDU-KATA, 2018)
Language is a language that secret transvestite and typical but they can also be called a community language although the existence of transvestites are always underestimated. Relating to the existence of a distinct language, this study was conducted to objectively describe the rules of word formation transvestites, transsexuals and said berimbuhan language acronym transvestites. Based on research that has been done found the following things. Rules of word formation transgender language is always changing but the rule could still be described is to keep taking one syllable to the original word and add sound- ong, -ece, -se, -es, -ika, -ra, and –ung on the last syllabe wich has been omitted. In addition to replacing the second syllable with a particle as above, the transvestites also created a language by adding sound in front of the home such as affixes-S1. To rule formation transvisitites acronym they use them by combining multiple patterns be some letters, combining syllable of two words, and combine the word of three or more words.